« Les grands-parents prennent la parole ! » : l’inclusion dans le cas du programme Abuelas y abuelos cuentacuentos de la Casa de la Literatura peruana à Lima - Hayakawa Casas, José; Vargas Pacheco, Cristina (Muséologies)

(untitled) (Association Québécoise de Promotion des Recherches Étudiantes en Muséologie (AQPREM), 2023)
For several decades, the museum has been reinventing itself in a democratic dynamic, as a forum and, more recently, as a laboratory, while waiting for the different types of publics, such as elderly people, a growing population, asking for aging assets inside institutions and the profit of their fundamental rights. These concerns have been addressed in a diverse and sustained approach based on international museological reflection.However, in Peru, political and academic attention to inclusion and accessibility in cultural fields, and more specifically in museums, is very recent. This is why this article focuses on the current state of participation of a population that has great potential, but which has not been examined in depth. This study, moreover, provides a mixed methodology (qualitative and quantitative) and multidimensional, with various techniques and research instruments such as the semi-fixed interview, the digital survey and the imaginary analysis form, with the participation of the program managers, its participants and specialists (one of them, an art historian and head of mediation and audiences in an art museum [MAC-Lima] and, the other, a university professor specializing in audience studies). Thus, the article is divided into two parts. First, we provide a historical, theoretical and contextual framework to show a general portrait of the participation of elderly people in Peruvian museums. Then we present the specific case of the «Storytelling grandparents» program at the House of Peruvian Literature (below CASLIT), between 2018 and 2022.